Foundations of Popfly : rapid mashup development - Griffin, Eric. (Berkeley, CA : Apress ; New York, NY : Distributed to the book trade by Springer-Verlag New York Inc., 2008)
Provides information on building custom mashups using Popfly.
Includes index.
Keywords: Mashups (World Wide Web); Web 2.0.; Web site development; World Wide Web; Web sites -- Design